Evaluation and Medical Management of Uncomplicated Diverticulitis - Langenfeld, Sean J. (Clinics in Colon and Rectal Surgery, 2021)
Uncomplicated diverticulitis is common, and its evaluation and treatment have evolved over time. Most patients present in a nontoxic manner with localized pain, leukocytosis, and reliable findings on computed tomography (CT). Healthy and stable patients are typically treated in the outpatient setting with very high rates of success. Recently, the necessity of antibiotic therapy has come into question, and several alternative agents have emerged, with the jury still out on their relative roles in diverticular disease. Currently, colonoscopy is still recommended after the resolution of an index episode of uncomplicated diverticulitis, and recurrence rates remain low. Several diet and lifestyle modifications have been shown to impact the rates of diverticulitis recurrence.
Keywords: uncomplicated diverticulitis; diverticulitis; medical management; mesalamine; probiotics